Pendidikan Kesehatan tentang Pencegahan Stroke pada Penderita Hipertensi di Kelurahan Legok Kota Jambi - Hasyim Kadri (3031-8572, 2022)
To be able to reduce the incidence of stroke in Indonesia, it can be done by increasing the knowledge of individuals, groups or communities about hypertension. Health education will affect knowledge as a medium-term outcome of health education. Furthermore, health knowledge will have an effect on increasing public health indicators as health education outputs. Objective To increase knowledge about stroke prevention, management and control of blood pressure. This series of activities was carried out in March - August 2022, in the Legok Village, Jambi City. The solution from this community service is to provide health education and stroke prevention simulations to change or increase public knowledge about stroke prevention including understanding, causes, signs and symptoms, prevention and management of stroke. To achieve this goal, the methods that will be used in these activities are discussions, counselling, simulations, role plays and literature studies. Health education is an effort to assist the community in overcoming their health problems through learning activities, thereby increasing knowledge and behaviour to prevent stroke. The results obtained A total of 15 people with hypertension took part in PKM activities. The participants were able to understand the material properly. Activity participants are able to simulate the material properly. And the participants of the activity were able to correctly answer questions related to the evaluation of the material